(untitled) - Norgaard, Richard L. (Belmont, Calif., 1964)
This book offers 58 cases that combine both the qualitative and quantitative aspects of financial management. The cases are based on real firms, real products, real individuals, and most importantly, real issues and offer a complete picture of the financial management process.
Keywords: Finance,Tài chính